ANALISIS NILAI TAMBAH DAN PELUANG KERJA AGROINDUSTRI TAHU DI KECAMATAN GADINGREJO - Rohmatul Uslah; Wuryaningsih Dwi Sayekti; Raden Hanung Ismono (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2022)
This study aims to determine the added value and job opportunities of the tofu agroindustry at Gadingrejo  Regency.  This research was conducted at Gadingrejo District using a census method.  Data consists of primary data and secondary data.  Primary data used include the use of raw materials, production facilities, tofu agroindustrial equipment, and the number of workers.  Primary data collection was carried out by interviewing 23 tofu agroindustries and 70 tofu-derived business units. Secondary data were literature study.  Secondary data includes Gross Regional Domestic Product and Number of Small and Medium Industry Actors at Pringsewu Regency.  The research data were analyzed descriptively and quantitatively to determine the added value and job opportunities of the tofu agroindustry.  The results showed that the age of the respondents varied greatly from the ages of 40 to 70 years.  The average use of raw materials for agroindustry for the small group is 40 kilograms, the medium group is 60 kilograms, and the large group is 150 kilograms in one production.  The tofu agroindustry at Gadingrejo District provides positive added value for this type of white tofu, namely IDR8,040.56 one kilogram of raw material or with an added value ratio of 51.73 percent.  There are 228 employment opportunities absorbed. Key words: added value, tofu, job opportunities